The ability of service quality in moderating transparency against muzakki's awareness of paying zakat - Mahyudin (Institute of Computer Science (IOCS), 2023)
Zakat is an obligation for Muslims and the responsibility of Muslims for the property they own. Handed over to managers who have been formed by the state with statutory regulations within the scope of statutory regulations, there are two organizations in managing zakat among the community. In North Sumatra, the zakat management body is referred to as North Sumatra BAZNAS having its address at Jl. Medan Estate Hajj Hospital, an institution where the people of North Sumatra province hand over their zakat wealth which entrusts the amil zakat agency in distributing and handing it over to people who become mustahiq. There is still a lack of public awareness in paying zakat, seen from the small amount of income each year compared to the number of Muslims in North Sumatra, which is 65%, although every year the receipt of zakat in Sumatra increases. Research Model used in this research is a tiered structure model and for test the proposed hypothesis is used SEM analysis technique (Structural Equation Modeling) which is operated via Partial Least Square (PLS) program. Transparency has a significant effect on muzakki's awareness of paying zakat, service quality affects muzakki's awareness of paying zakat, service quality does not moderate or does not strengthen and weaken the effect of transparency on the quality of muzakki's awareness of paying zakat